(untitled) (Zaporizhzhia Historical Review, 2021)
The place of Zaporizka Sich in Russian-Turkish commerce in the 60-ies of the XVIIIth century is being defined. It is also shown that in the notes by Kursk merchant Mykhaylo Odnoryadkin, written in the 60-ies of the XVIIIth century, the modern state of Russian-Turkish trade relationship and its main problems are being characterized from the point of view of direct participant of this trade, personally interested in settling this direction of foreign commerce.